Why Waco? : cults and the battle for religious freedom in America - Tabor, James D., 1946- (University of California Press, 1995)
In the first balanced, authoritative account of the siege, James Tabor and Eugene Gallagher explore the powerful drama in Waco and the motivations of all the players, including the government, the media, the cultbusters, the Branch Davidians, and David Koresh himself. Tabor and Gallagher unflinchingly confront the most controversial accusations concerning the group's possession of illegal firearms, unconventional sexual practices, and child abuse. Without attempting to excuse Koresh's actions, they argue that the public has never been given the complete story. Tabor and Gallagher explain what really happened in Waco: Who were the Branch Davidians and what originally brought them to Mount Carmel? What led the government to attack? What role did the media play? And what lessons must we learn to avoid repeating this American tragedy?
Keywords: Koresh, David, -- 1959-1993.; Branch Davidians.; Koresh, David, -- 1959-1993; Branch Davidians; Davidianer; Davidiens -- Waco (Etats-Unis) -- 1993.; Koresh, David.; Waco Branch Davidian Disaster, Tex., 1993.; Cults -- United States.; Affaire de la secte des Davidiens de Waco, Waco, Tex., 1993.; Cultes -- États-Unis.; RELIGION -- Eckankar.; BODY, MIND & SPIRIT -- New Thought.; RELIGION / Comparative Religion; Cults; Texas; United States; Massensuizid; Sekten.; Liberté de conscience -- États-Unis.; Waco, Affaire de la secte davidienne de (1993); Sectes -- États-Unis.; Waco, Affaire de la secte dravidienne de (1993); nouveau mouvement religieux -- Koresh, David -- Etats-Unis.; Cults.; 1993; Sects.; Texas.